Effect of Different Processing Methods on the Millet Polyphenols and Their Anti-diabetic Potential - Wang, Han; Fu, Yongxia; Zhao, Qingyu; Hou, Dianzhi; Yang, Xuehao; Bai, Shuqun; Diao, Xianmin; Xue, Yong; Shen, Qun (Frontiers in Nutrition, 2022)
Interest in polyphenols has grown due to their beneficial effect on diabetes attenuation. Millets are ancient crops that are rich in polyphenols and used for both food and feed. They are grown worldwide and are adapted to production under dry, hot conditions. The polyphenols found in millets have anti-diabetic properties. However, millet is usually consumed after being processed by heating, germination, fermentation, and other processing methods, which may alter polyphenol content and thus affect their anti-diabetic potential. This mini-review profiles the effects of different processing methods on millet polyphenols and how changes in millet polyphenols affect the hypoglycemic effect of millet. Future studies are needed to compare the anti-diabetes potential of millet polyphenols before and after processing and to explore ways to minimize polyphenol losses and thus maintain their hypoglycemic effect in final products.